Pengaruh Rendaman Air Hangat Pada Kaki Terhadap Tingkat Insomnia Pada Lansia Di Puskesmas Desa Terjun Tahun 2023 - Endryani Syafitri; Muthia Sari Mardha; Rini Syahrani (Journal of Pharmaceutical and Sciences, 2023)
Background: Insomnia in the elderly population is generally associated with physical and psychological factors when the body begins to experience vulnerability and mental well-being becomes less stable. Many elderly individuals face these changes unprepared, leading to mental burdens that ultimately affect sleep quality and potentially trigger insomnia issues. Objective: to find out the effect of soaking feet in warm water on the level of insomnia in the elderly at the Puskesmas Waterfall Village before and after soaking in warm water in the experimental and control groups. Methods: quasi-experiments with unequal control groups. The sample consisted of 20 respondents who were divided into 2 groups, namely 10 experimental groups and 10 control groups. Using univariate and bivariate data analysis with a parametric test, namely paired sample T-test. Results: the mean insomnia after a warm bath in the experimental group was 1.60, while in the control group (post-test) it was 2.00 with a mean difference of -1.400 and a p-value of 0.050 (=0.05). Conclusion: showed that the effect of a warm bath on the level of insomnia was different in the experimental and control groups. Elderly people are advised to do it 2 times a week to reduce insomnia.